Identification of Differentially Expressed Genes Reveal Conserved Mechanisms in the Rice-Magnaporthe oryzae Interaction - Liang, Dong; Qi, Zhongqiang; Du, Yan; Yu, Junjie; Yu, Mina; Zhang, Rongsheng; Cao, Huijuan; Pan, Xiayan; Qiao, Junqing; Song, Tianqiao; Liu, Youzhou; Chen, Zhiyi; et al. (Frontiers in Plant Science, 2022)
Magnaporthe oryzae causes rice blast disease and is responsible for major losses in rice production worldwide. Although numerous studies have focused on the interactions between Oryza sativa and Magnaporthe oryzae, to date, the conserved mechanisms remain in part unclear. In this study, a comparative analysis of transcriptomes of Oryza sativa L. ssp. japonica cv. ‘Nipponbare’ interacted with three M. oryzae strains (248, 235, and 163) were investigated to explore the conserved molecular mechanisms. Differentially expressed genes with similar expression patterns in the interactions between cultivar ‘Nipponbare’ and three M. oryzae strains were defined as Conserved Differentially Expressed Genes (CDEGs). These included 3,647 O. sativa CDEGs and 3,655 M. oryzae CDEGs. Of the 3,647 rice CDEGs, four CDEGs (LOC_Os03g19270, LOC_Os07g36600, LOC_Os05g28740 and LOC_Os01g32780) encode universal stress protein (USP) and were induced within 24 hours post-inoculation (hpi) by three M. oryzae strains. Meanwhile, overexpression of LOC_Os07g36600 result in slow disease response to rice blast. Furthermore, four rice genes coding Light-harvesting chlorophyll a/b-binding protein (LHC) (LOC_Os02g52650, LOC_Os09g12540, LOC_Os11g13850, LOC_Os05g22730) were also identified as CDEGs and induced at 48 hpi, which might contribute to blast resistance through ROS accumulation combined result of previous publications. In M. oryzae, MoCDIP4, the gene coding known virulence-associated proteins, owns more homologous genes than that of other effector coding genes. Seven homologous genes of MoCDIP4 were found belong to AA9 CAZyme subfamily and were continuously up-regulated across all infection stages. This study uncovered that genes required for conserved mechanisms of rice-M. oryzae interaction, which include rice USP genes, rice LHC genes and M. oryzae AA9 genes. This study will help us to understand how O. sativa responds to M. oryzae infections and the molecular mechanisms of M. oryzae pathogenicity.